(untitled) (Economic Journal of Nepal, 2017)
This study aims to examine the impact of corruption on economic growth in Nepal for the period 2004 - 2017. The result of the regression analysis shows that there is a negative relationship between the dependent variable (GDP) and corruption level in Nepal. This means that as the level of corruption activities increases, economic growth decreases significantly. Based on the findings, the study therefore recommend as follows: The activities of the anticorruption agencies in Nepal such as The Commission for the Investigation of Abuse of Authority (CIAA) should be strengthened; the public should be educated about the problems that corrupt practices create for the economy and the society at large, and be discouraged from participating incorrupt practices. Nepal should put in leadership positions honest individuals who would serve as role models to minimize the negative consequences of corruption with its negative impact on the development and growth of Nepal; corruption is easily growing in Nepal because government involvement in economic decision making is high.